Colonised-Coloniser Relations: An Exploration Of Algerian Literature's Depiction Of The Intricate Dynamics Between Colonised Algerians And The Colonising French (El-Wahat Journal for Research and Studies, 2025)
This study delves into the representation of colonised-coloniser interactions within Algerian literature, scrutinizing the intricate dynamics between the colonised Algerians and their French colonisers both during and post the colonial era. Emphasis is placed on selected masterpieces by three distinguished Algerian novelists: Kateb Yacine, Mohammed Dib, and Rachid Mimouni. Yacine's Nedjma (1956) employs an avant-garde, non-linear narrative combined with poetic diction to capture the Algerian populace's challenges and dreams in the face of French dominion. Dib's La Grande Maison (1952) traverses the tribulations endured by the Algerians amidst World War II, accentuating motifs of destitution, subjugation, and the quest for emancipation. Mimouni's The Honor of the Tribe (1989) delves into post-independence Algeria, unravelling the multifaceted Algerian Civil War and colonialism's enduring impact. Through their eclectic literary methodologies and genres, these writers illuminate diverse facets of colonised-coloniser interactions, encompassing subjugation, defiance, brutality, trauma, selfhood, remembrance, and conciliation. The study further elucidates how these literary maestros mirror the historical and political episodes molding these interactions, particularly spotlighting the Algerian War of Independence and the subsequent Algerian Civil War. Additionally, the research broaches cultural and linguistic challenges spawned by these interactions, encompassing bilingualism, cultural amalgamation, and translational intricacies. In its progression, the study interrogates and contests the colonial portrayal and discourse surrounding Algeria and its inhabitants. Concludingly, prospects for dialogue and mutual collaboration between post-colonial Algeria and France are explored. Ultimately, Algerian literary works present an invaluable lens, offering profound insights into the multifarious and evolving nature of colonised-coloniser relationships.Keywords: Algerian literature, Colonised-coloniser dynamics, Colonialism and post-colonialism, Literary methodologies and genres, Algerian-French dialogue